Skin and Gut: Psoriasis and irritable bowel syndrome. Is there an association? (Annals of Medical Research, 2021)
Aim: The frequent occurrence of psoriasis with gastrointestinal system diseases indicates that psoriasis may also be associated with IBS. We aimed to evaluate the frequency of irritable bowel syndrome in patients with psoriasis and psoriatic arthritis.Material and Methods: Study included 111 patients with psoriasis, and 214 healthy volunteers. The presence of IBS in the psoriasis and control groups was evaluated according to the Rome III diagnostic criteria (Recurrent abdominal pain or discomfort at least 3 days/month in the last 3 months associated with two or more of the following: Improvement with defecation, onset associated with a change in frequency of stool, onset associated with a change in form (appearance) of stool). The participants were also asked about the presence of findings supporting the diagnosis of IBS. The participants were asked about the frequency of defecation, and the stool type was evaluated according to the Bristol stool form scaleResults: 41 (36.9%) patients in the psoriasis group and 27 (12.6%) controls were detected to have IBS( p 0.001). Passage of mucus, abdominal distension, and straining were found more frequently in the psoriasis group than in the control group (p = 0.023, 0.001, and 0.001, respectively). The mean defecation frequency per week was significantly higher in the psoriasis group than in the control group (p = 0.000). The mean value for the Bristol stool scale was 4.12 ± 1.13 for the psoriasis group and 3.72 ± 1.16 for the control group (p = 0.003).Conclusion: The increased frequency of IBS and the findings supporting the diagnosis of IBS in these patients suggest that they have a tendency to develop IBS. The indication of a higher frequency of IBS in patients with psoriatic arthritis is another important outcome of the present study.
Keywords: Functional disorder; irritable bowel syndrome; psoriasis